Revealing the switching mechanisms of an off–on–off fluorescent logic gate system. Issue 30 (22nd July 2019) - Chi, Weijie; Chen, Jie; Qiao, Qinglong; Gao, Ying; Xu, Zhaochao; Liu, Xiaogang
Abstract : We showed that TICT and PET were responsible for the off–on–off switching mechanisms of a fluorescent molecular logic gate. Abstract : A deep understanding of fluorescence on–off and off–on switching mechanisms is the foundation for rationally designing highly effective molecular logic gate components and systems. These mechanisms, however, are often subtle to perceive and interpret, as multiple effects may contribute to the change of fluorescence signals. Herein, we systematically investigated the 'off–on–off' switching mechanisms of a fluorescent logic gate moleculeM1 using density functional theory (DFT) and time-dependent DFT (TD-DFT). Based on photoexcitation and photoemission calculations, and potential energy surface scans in the excited state, we have shown that as the pH of the medium continuously decreases and the sequential protonation of the molecule takes place, the prevention of twisted intramolecular charge transfer (TICT) followed by the activation of photo-induced electron transfer (PET) was responsible for the off–on–off switching mechanism ofM1 . Our results provided new insights for understanding the 'off–on–off' phenomenon inM1 . The good agreement between theoretical calculations and experimental observations also suggests that computational chemistry is a powerful tool to aid the molecular design and engineering of fluorescent logic gate compounds.